(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
Most of the people living in Uzbekistan believe in Islam. Child education in all Uzbek families is based on national traditions and Islamic values. If we consider that national values are customs that have been going on since time immemorial, on the other hand, we can see that religious values are mixed with them and form a mutual unity. As education is directly connected with national and religious values, the demand for publications of religious literature in the Uzbek language is increasing.